1986
DOI: 10.1246/cl.1986.315
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Rearrangement of Tetrahydrodicyclopentadiene to Adamantane Over Y-Zeolite

Abstract: Bifunctional rare-earth exchanged Y zeolite, has the high catalytic activity for the synthesis of adamantane from tetrahydrodicyclopentadiene in the presence of hydrogen and hydrogen chloride, in a fixed bed flow system. The catalyst deactivated by pore plugging with deposited hydrocarbons can be almost completely regenerated by hydrocracking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…In adamantane production catalyzed by Y zeolites, hydrogenolysis and various kinds of ring opening reations also take place simultaneously in the presence of hydrogen [10][11][12]. In our experiment, without hydrogen few hydrogenolysis and various kinds of ring opening reations occurred.…”
Section: Isomerization Of Tetrahydrodicyclopentadienementioning
confidence: 46%
See 2 more Smart Citations
“…In adamantane production catalyzed by Y zeolites, hydrogenolysis and various kinds of ring opening reations also take place simultaneously in the presence of hydrogen [10][11][12]. In our experiment, without hydrogen few hydrogenolysis and various kinds of ring opening reations occurred.…”
Section: Isomerization Of Tetrahydrodicyclopentadienementioning
confidence: 46%
“…Considering reaction data, higher Si/Al ratio contributes little to the formation of exo-THDCPD, while favor the formation of adamantane and other byproducts. In the adamantane literature [10][11][12], it was suggested that strong Bronsted acid sites help the formation of adamantane and side reactions. From this point, H-USY with more moderate acidity is favorable choice for exo-THDCPD production.…”
Section: The Module Of Zeolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid the environmental problems associated to the use of aluminum chloride as catalyst, the application of environmentally solid acid as isomerization catalysts would be highly desired. Few reports can be found in the literature studying the use of zeolites for the adamantane synthesis, being zeolite Y the preferred catalyst (36)(37)(38).…”
Section: Reaction Involving a Ts With Similar Size That The Reaction mentioning
confidence: 99%
“…rearrangement of endo-TCD [8,9]. However, the low activity of zeolites limits its industrial application.…”
Section: Introductionmentioning
confidence: 99%